Distribution of Salmonella Serotypes in Fish in Retail Trade in Kochi - V., Narayanan Nambiar; K., Mahadeva Iyer (Fishery Technology, 2025)
This study assesses the prevalence of salmonella and the distribution of different serotypes in fresh as well as frozen fish in retail trade in Cochin. 5.76% of the 156 fresh fish and 8.66% of the 127 frozen fish sampleswere found to be contaminated withSalmonella. The 32 st:rains of salmonella isolated belonged to 16 different serotypes and these included a few very rarely occurring serotypes like S. adelaide, S. barendrup, S. chingola, S. cerro, S. nchanga, S. oslo and S. mbandaka. Three serotypes namely, S. barendrup, S. emek and S. adelaide were isolated from fresh as well as frozen fish samples, and others were isolated from either fresh or frozen fish samples.